2018
DOI: 10.1002/slct.201801559
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Clauson‐Kass and Paal‐Knorr Pyrrole Synthesis Using β‐Cyclodextrin‐SO3H under Aqueous and Neat Conditions ‐ Application to Formal Synthesis of Polygonatine

Abstract: The synthesis of pyrroles under mild conditions using sulfonic acid‐functionalized β‐Cyclodextrin (β‐CD) as a supramolecular catalyst under aqueous conditions is demonstrated. Good to excellent conversion of various amines into pyrroles was observed without any side product formation. CD was found to play a dual role as a phase transfer reagent through inclusion as well as an acid catalyst thereby facilitating the smooth conversions of reactants. The advantages of this protocol are mild reaction conditions, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Besides these, it also is a promising alternative to the conventional organic solvents, owing to which numerous research groups over the past decades have explored the prodigious potential of water as the reaction medium. , Thus, the development of water-compatible catalysts for the establishment of eco-friendly sustainable protocols are the need of the hour. Therefore, taking into account of the aforementioned advantages of metal-free protocols under aqueous conditions and the drawbacks of existing regime of catalysts, in continuation to our efforts to develop sustainable protocols using benign catalysts, we herein report a biomimicking process wherein polydopamine is used as an organocatalyst for the oxidation of benzylic primary amines, alkyl amines and secondary amines aerobically. The formed intermediate imines are trapped by diamines (or) amides and aerobically oxidized to afford nitrogen heterocycles such as benzimidazoles, quinoxalines, and quinazolinones, as well as other heterocycles such as quinolines and indole via a domino/cascade process (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides these, it also is a promising alternative to the conventional organic solvents, owing to which numerous research groups over the past decades have explored the prodigious potential of water as the reaction medium. , Thus, the development of water-compatible catalysts for the establishment of eco-friendly sustainable protocols are the need of the hour. Therefore, taking into account of the aforementioned advantages of metal-free protocols under aqueous conditions and the drawbacks of existing regime of catalysts, in continuation to our efforts to develop sustainable protocols using benign catalysts, we herein report a biomimicking process wherein polydopamine is used as an organocatalyst for the oxidation of benzylic primary amines, alkyl amines and secondary amines aerobically. The formed intermediate imines are trapped by diamines (or) amides and aerobically oxidized to afford nitrogen heterocycles such as benzimidazoles, quinoxalines, and quinazolinones, as well as other heterocycles such as quinolines and indole via a domino/cascade process (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Kumar and co-workers explored the synthesis of Nsubstituted pyrroles using cyclodextrin as a supramolecular catalyst under neat conditions. [88] They used sulfonic acidfunctionalized β-cyclodextrin (β-CD) moiety as the catalyst. It was reported that moderate to good yields of products were obtained without any side products.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Kumar and co‐workers explored the synthesis of N ‐substituted pyrroles using cyclodextrin as a supramolecular catalyst under neat conditions [88] . They used sulfonic acid‐functionalized β ‐cyclodextrin (β‐CD) moiety as the catalyst.…”
Section: Miscellaneousmentioning
confidence: 99%
“…However, the yield is quite low (o20%) and the reaction temperature is high (300-600 1C). [18][19][20][21] Cao et al successfully used biomass platform small molecules such as 2,5-hexanedione, 22,23 2,5-dimethoxytetrahydrofuran 24,25 or 2,5-dimethylfuran 26 as raw materials, which could furnish high catalytic amination activity under mild conditions (480% yield). Catalytic conversion of biomass sugars via 5-hydroxymethylfurfural to 2,5-dimethylfuran has been extensively reported, which ensures that the source of 2,5-dimethylfuran and relevant furanic compounds is sustainable.…”
Section: Introductionmentioning
confidence: 99%